STRATEGI GURU PENDAMPING KHUSUS (GPK) DALAM MENINGKATKAN KARAKTER MANDIRI PADA PESERTA DIDIK BERKEBUTUHAN KHUSUS (PDBK) KELAS SUMBER DI SMPN 43 SURABAYA - Bekti, Aghis Arwa; Listyaningsih (Kajian Moral dan Kewarganegaraan, 2025)
This study aims to identify the strategies used by special assistant teachers (GPK) in developing the independent character of students with special needs (PDBK) in the resource class at SMPN 43 Surabaya, as well as the challenges they face. The results are analyzed using Albert Bandura's social learning theory. This is a qualitative study with a phenomenological research design. The research informants were GPK in the resource class at SMPN 43 Surabaya. The findings show that the strategies implemented by GPK to enhance the independent character of PDBK include: (1) habituation in daily activities; (2) development of independence through modeling in the form of vocational skills and self-care; (3) guidance in contextual learning through in-class and out-of-class activities; and (4) collaboration with parents or guardians of students. The challenges faced by GPK involve differences in students' abilities and needs, as well as lack of support from the external environment. Bandura's theory explains that the teacher’s behavior model influences PDBK through four processes: (1) attention, where PDBK observe the teacher's behavior; (2) retention, where PDBK remember the teacher’s behavior; (3) reproduction, where PDBK attempt to imitate the behavior demonstrated by the teacher related to independence; and (4) motivation, where the teacher encourages PDBK to continue developing independence and to repeat observed behavior. These four processes form the foundation for understanding how GPK strategies gradually and sustainably build the independent character of PDBK